High discordance in blood and genital tract HIV-1 drug resistance in Indian women failing first-line therapy. (24th May 2018) - Saravanan, Shanmugam; Gomathi, Selvamurthi; Delong, Allison; Kausalya, Bagavathi; Sivamalar, Sathasivam; Poongulali, Selvamuthu; Brooks, Katherine; Kumarasamy, Nagalingeswaran; Balakrishnan, Pachamuthu; Solomon, Sunil S; Cu-Uvin, Susan; Kantor, Rami
Abstract: Objectives: Examine HIV-1 plasma viral load (PVL) and genital tract (GT) viral load (GVL) and drug resistance in India. Methods: At the YRG Centre for AIDS Research and Education, Chennai, we tested: PVL in women on first-line ART for ≥6 months; GVL when PVL >2000 copies/mL; and plasma, genital and proviral reverse transcriptase drug resistance when GVL >2000 copies/mL. Wilcoxon rank-sum and Fisher's exact tests were used to identify failure and resistance associations. Pearson correlations were calculated to evaluate PVL–GVL associations. Inter-compartmental resistance discordance was evaluated using generalized estimating equations. Results: Of 200 women, 37% had detectable (>400 copies/mL) PVL and 31% had PVL >1000 copies/mL. Of women with detectable PVL, 74% had PVL >2000 copies/mL, of which 74% had detectable GVL. Higher PVL was associated with higher GVL. Paired plasma and genital sequences were available for 21 women; mean age of 34 years, median ART duration of 33 months, median CD4 count of 217 cells/mm 3, median PVL of 5.4 log10 copies/mL and median GVL of 4.6 log10  copies/mL. Drug resistance was detected in 81%–91% of samples and 67%–76% of samples had dual-class resistance. Complete three-compartment concordance was seen in only 10% of women. GT–proviral discordance was significantly larger than plasma–proviral discordance. GT or proviral mutations discordant from plasma led to clinically relevant resistance in 24% and 30%, respectively. Conclusions: We identified high resistance and high inter-compartmental resistance discordance in Indian women, which might lead to unrecognized resistance transmission and re-emergence compromising treatment outcomes, particularly relevant to countries like India, where sexual HIV transmission is predominant.